The Strategic Role of Pancasila Education in Easing the Adverse Impact of Online Loans on the Young Generation in the Era of Society 5.0 - Arwiyah, Yahya; Sofyan, Edy (JURNAL SOCIAL LIBRARY, 2023)
Online lending has become a popular option, particularly among the younger generation in today's digitalized society. However, many young people are not fully aware of the economic, social, and psychological implications that come with using online loans. This research suggests that Pancasila Education can be an effective solution to provide young people with a comprehensive understanding of the impact of online lending. Through qualitative research methods and interviews, this study investigates young people's firsthand experiences with online loans and gathers insights from experts in education and economics. The findings reveal that Pancasila Education plays a crucial role in shaping the younger generation's understanding of moral and ethical values in personal financial management. By internalizing values of responsibility and understanding the consequences of financial decisions, including the use of online loans, young people can develop a responsible character and behavior in dealing with financial challenges in the digital era. These findings have practical implications for developing focused education programs to protect the well-being of the younger generation in the face of the evolving dynamics of modern society.